The effects of potassium bromate and resveratrol on cholesterol and vitamin E levels in heart, muscle and brain of wistar rats - Keser, Serhat; Yilmaz, Okkes; Tuzcu, Mehmet (My University, 2010)
Resveratrol is a phytoalexin, highly abundant in skins of red grapes, peanuts and blueberries. The aim of this study was to examine the effects of resveratrol and kidney carcinogen potassium bromate on the levels of vitamin E and cholesterol in heart, muscle and brains of old female Wistar rats. All analyses were measured by high performance liquid chromatography. According to our results, retinol, vitamin D3, ?-tocopherol and cholesterol levels were decreased in the K and R groups when compared to C group (p<0.01, p<0.05, p<0.05, p<0.05, respectively) in the heart. Vitamin D3, ?-tocopherol, ?-tocopherol acetate and cholesterol levels were decreased in the R group (p<0.05, p<0.001, p<0.001, p<0.001, respectively) in the muscle. The level of cholesterol was decreased in the K and R groups when compared to C group (p<0.05) in the brain. In conclusion, our results indicated that the applications of potassium bromate and resveratrol influenced cholesterol and vitamin E levels and these applications can be affected cholesterol biosynthesis in old female wistar albino rats.
Keywords: Cholesterol; Heart; Muscle; Potassium Bromate; Resveratrol